Determination of natural vibrations of piecewise homogeneous viscoelastic bodies using the ANSYS software package - Kligman, Evgeny Petrovich; Matveenko, Valery Pavlovich; Sevodina, Natalia Vital'evna (Computational Continuum Mechanics, 2010)
This paper considers algorithms which make use of the capabilities of the ANSYS software package for the solution of the problem of natural vibrations of piecewise homogeneous viscoelastic bodies, whose mechanical behavior is described by linear viscoelastic equations. The main merit of these algorithms is that they permit application of the ANSYS finite element procedures to new mechanical problems. We present two algorithms. One of the algorithms specifies the sequence of ANSYS-based operations which reduce the problem of natural vibrations of piecewise homogeneous viscoelastic bodies to its algebraic analog. The other is based on the idea of constructing the solution of the problem under study as a linear combination of natural vibration modes of a corresponding elastic body, which are found using the ANSYS software package.
Keywords: natural vibrations; viscoelasticity; finite element method; software ANSYS; method of principal coordinates